Rollercoaster: changes and challenges to Denmark’s NATO engagement - Ringsmose, Jens; Rynning, Sten (Politica, 2017)
Danish foreign policy activism appears most clearly in a NATO context. The Atlantic Alliance is first and foremost the vehicle through which Denmark contributes to ensuring US engagement in European security politics. NATO is the mechanism that enables Denmark to establish close military relations with select allies, which in turn facilitates Danish military contributions to international operations. Finally, NATO is a lever for a broader European foreign policy that Denmark has difficulties pursuing because of her EU opt-out. However, Danish NATO activism has varied over time. It was increasing, then very significant, and in recent years it has been declining. Currently, it might be on its way up again. These fluctuations must be interpreted as the result of the political will to pursue the activism that is made possible by the international environment. We analyze the political will to pursue NATO activism from 1990 to 2017; we focus on the national willingness to carry security political burdens.